Pengaruh Pengembangan Karier, Penempatan Jabatan Dan Motivasi Terhadap Prestasi Kerja Pegawai Pada Dinas Lingkungan Hidup dan Pertanahan Provinsi Sumatera Selatan - Muhammad Kurniawan; Santi Puspita; Riski Panduwinata (Universitas PGRI Palembang, 2022)
ABSTRACTÂ In facing the challenges in the era of globalization, it is necessary to find an explanation on how to make improvements and improvements and improve the performance of Civil Servants (PNS). At the Office of the Environment and Land Service of the Province of South Sumatra, the placement of employees in positions has not shown compatibility between positions, educational backgrounds, and an example is the placement of job positions that are not in accordance with the last Employee Education Graduate the researchers are interested in conducting research with